Update on Hedgehog Pathway Inhibitor Therapy for Patients with Basal Cell Naevus Syndrome or High-frequency Basal Cell Carcinoma - Babette J.A. Verkouteren; Kelly A.E. Sinx; Marie G.H.C. Reinders; Maureen J.B. Aarts; Klara Mosterd (Acta Dermato-Venereologica, 2022)
Some patients with basal cell carcinoma develop a large number of basal cell carcinomas during their lives. The most common underlying genetic disease that causes multiple basal cell carcinomas is basal cell naevus syndrome. Basal cell naevus syndrome is caused by a germline mutation in patched-1 (PTCH1), a tumour suppressor gene of the hedgehog signalling pathway. However, in a significant portion of patients with multiple basal cell carcinomas, no underlying genetic cause is found. Nevertheless, these patients can experience a treatment burden comparable to that of patients with basal cell naevus syndrome. They are referred to as high-frequency basal cell carcinoma patients. Hedgehog pathway inhibitors were the first group of targeted therapy for basal cell carcinomas. This study reviews the literature on hedgehog pathway inhibitor therapy for patients with basal cell naevus syndrome or high-frequency basal cell carcinoma, to provide an overview on efficacy, safety, dosing regimens, tumour resistance and reoccurrence, and health-related quality of life.